Think Aloud - to facilitate reflective practice for cross-country coaches - Lunde, G. A.; Pettersen, J. N. (Book of Abstracts. 4th Nordic Winter Sports Conference "Performance in snow sports: Translating science into practice" 3rd-4th October, 2022, Mid Sweden University, Campus Östersund, Sweden, 2022)
Reflective practice has been identified as a key in coach development and it has been argued that reflective practice should be central to coach education programmes. Think Aloud has been used successfully to develop self-awareness and reflection in coaches` practice. TA is recognized for offering the potential to personalise reflective practice, it enables the coach to engage in a reflective process that is specific for the coach and the coaching context. Un til now, no studies regarding TA have been identified for the Nordic skiing disciplines. The aim of this incipient project is to explore the potential impact of the TA protocol on both the reflective and professional practice of elite cross-country coaches. The study will be con ducted as a qualitative intervention study according to the well-established TA protocol of seven stages developed by Ericsson and Simon.The purpose of the project is to find out to what extent TA can help coaches to: • focus on the athletes and individualize based on the athletes` level, ambitions and pre requisites • observe, systematise, analyse, intervene and give feedback • involve, share responsibility and ensure that practitioners reflect on their own develop ment and achievements. The presentation will focus on how TA can be used successfully to develop self-insight and reflection in the trainer`s practice and invites others to participate to ensure an international anchoring.